(untitled) (Research, Society and Development, 2022)
Errors can occur at any stage of drug therapy. Potentially dangerous drugs are worth mentioning because they are more likely to harm the patient, especially children, as they have particularities inherent to their age. We sought to identify barriers that reduce errors with potentially dangerous medications in hospitalized children. This is an integrative review, whose search took place between August and September 2020, in the Cochrane Library, PUBMED, Google Scholar databases, and in the TRIP DATABASE meta-searcher, to answer the guiding question: “What are the interventions in reducing of errors with potentially dangerous drugs in hospitalized children?”. Searches in the researched databases captured 298 references. After the exclusions, 76 studies were selected to be read in full; of these, 6 articles were selected to compose this review. They were grouped into three categories: Educational strategies; Technological resources and; Assistance activities. The studies address several strategies for reducing medication errors. Here, the importance of combining strategies for the safe use of potentially dangerous drugs in children is highlighted.